2019
DOI: 10.1145/3319445
|View full text |Cite
|
Sign up to set email alerts
|

Using Informed Design in Informal Computer Science Programs to Increase Youths’ Interest, Self-efficacy, and Perceptions of Parental Support

Abstract: Our work is situated in research on Computer Science (CS) learning in informal learning environments and literature on the factors that influence girls to enter CS. In this article, we outline design choices around the creation of a summer programming camp for middle school youth. In addition, we describe a near-peer mentoring model we used that was influenced by Bandura's self-efficacy theory. The purpose of this article, apart from promoting transparency of program design, was to evaluate the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…We build on existing work in informal computing programs for youth [8,19,50,67]. Research findings highlight the need for creation and delivery of curriculum that is not only administered by facilitators who are technically competent, but who also look like the youth they are serving or who are trained to be socially-just educators [50,67].…”
Section: Informal Computing Educationmentioning
confidence: 99%
See 3 more Smart Citations
“…We build on existing work in informal computing programs for youth [8,19,50,67]. Research findings highlight the need for creation and delivery of curriculum that is not only administered by facilitators who are technically competent, but who also look like the youth they are serving or who are trained to be socially-just educators [50,67].…”
Section: Informal Computing Educationmentioning
confidence: 99%
“…Past initiatives have focused on creating affinity-oriented learning environments, providing women role models, and teaching girls through projectbased learning [33]. Clarke-Midura et al [8] examined a summer informal learning program with the interest in broadening the participation of girls in computing. Their findings highlight the role of near-peer mentors in influencing a positive change in campers interest and self-efficacy.…”
Section: Informal Computing Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of this theory, Wang defines self-efficacy as "an individual"s judgment of his or her own ability to complete an action required of a certain type of performance" (Wang, 2013, p. 666). Clarke-Midura et al (2019) found significant gains using an informal learning environment to increase interest in computer science…”
Section: Introductionmentioning
confidence: 99%